Distribution of Choroidal Thinning in High Myopia, Diabetes Mellitus, and Aging: A Swept-Source OCT Study. (15th August 2019) - Bartol-Puyal, Francisco de Asís; Isanta, Carlos; Ruiz-Moreno, Óscar; Abadia, Beatriz; Calvo, Pilar; Pablo, Luis
Abstract : Purpose . To compare the macular choroidal thinning between young healthy, aged healthy, young high myopic, and aged type 2 diabetic (T2D) patients using the Early Treatment Diabetic Retinopathy Study (ETDRS) grid and three-dimensional (3D) maps. Methods . A prospective study including 102 eyes of 51 healthy young subjects, 60 eyes of 30 healthy aged subjects, 24 eyes of 12 high myopic patients, and 110 eyes of 55 T2D patients. Choroidal thickness (CT) was examined with swept-source optical coherence tomography Triton DRI (Topcon Corporation, Tokyo, Japan). The choroid was automatically segmented using the software algorithm, and mean CT values of a 6 × 6 mm macular cube were exported. 3D maps were created to represent CT, and its values were compared using the ETDRS grid. Results . Mean age was 27.31 ± 3.95, 66.41 ± 7.54, 27.69 ± 3.89, and 66.48 ± 7.59 years in young healthy, aged healthy, young high myopic, and T2D patients, respectively. CT was not shown to be uniform, as superior and central zones were thicker. All ETDRS sectors were always thicker (p < 0.05 ) in young healthy individuals than in the others. It was found that the choroidal sector which got thinner was inferior in case of age (103.28 μ m decrease), inferior-nasal in high myopia (86.19 μ m decrease), and temporal in T2D (55.57 μ m decrease). In addition, the choroid got thinner in those regions where it was thicker in healthy subjects. Conclusions . 3D maps allow a further comprehension of choroidal changes. The choroidal pattern in young healthy individuals resembles a mountain range; with age, a mountain peak; in high myopia, an inverted gorge; and in aged T2D, gathered hills. Not all choroidal regions are affected in a similar way, as it depends on the pathology. The thicker the zone is in healthy subjects, the thinner it becomes with any pathology.